Graphene oxide reduction by solid-state laser irradiation for bolometric applications. (18th December 2017) - Kondrashov, Vladislav A; Struchkov, Nikolay S; Rozanov, Roman Yu; Nevolin, Vladimir K; Kopylova, Daria S; Nasibulin, Albert G
Abstract: We present a method for reduced graphene oxide (GO) patterning on the surface of GO film by a 445 nm solid-state laser with the adjustable fluence from 0.2–20 kJ cm −2 . We demonstrate that the optimal argon concentration in air to obtain good quality reduced GO films is 90%. Varying the laser irradiation energy density allows controlling the resistance and I G / I D and I G / I 2 D ratios of Raman peak intensities. As a result, we demonstrate the possibility of forming of conductive patterns with a sheet resistance of 189 Ohm/□ and ∼1 μ m film thickness by a local reduction of the GO. The fabricated structures reveal excellent bolometric response with a high speed and sensitivity to the radiation in the visible wavelength region.